2004
DOI: 10.3748/wjg.v10.i21.3225
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of PTEN is associated with increased angiogenesis and VEGF overexpression in gastric cancer

Abstract: Our results imply that inactivation of PTEN gene and over-expression of VEGF contribute to the neovascularization and progression of gastric cancer. PTEN-related angiogenesis might be attributed to its up-regulation of VEGF expression. PTEN and VEGF could be used as the markers reflecting the biologic behaviors of tumor and viable targets in therapeutic approaches to inhibit angiogenesis of gastric cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…PTEN related angiogenesis might be attributed to its up-regulation of VEGF expression for their report. PTEN and VEGF could be used as the markers reflecting the biologic behaviors of tumor and viable targets in therapeutic approaches to inhibit angiogenesis of gastric cancers (Zhou et al, 2004). In our study we didn't find any correlation between VEGF and PTEN expression.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…PTEN related angiogenesis might be attributed to its up-regulation of VEGF expression for their report. PTEN and VEGF could be used as the markers reflecting the biologic behaviors of tumor and viable targets in therapeutic approaches to inhibit angiogenesis of gastric cancers (Zhou et al, 2004). In our study we didn't find any correlation between VEGF and PTEN expression.…”
Section: Discussioncontrasting
confidence: 58%
“…OS difference was not found between PTEN, VEGF, HER2, p53 expression rates in our study. Zhou et al (2004) reported that inactivation of PTEN gene and over-expression of VEGF contribute to the neovascularization and progression of gastric cancer. PTEN related angiogenesis might be attributed to its up-regulation of VEGF expression for their report.…”
Section: Discussionmentioning
confidence: 99%
“…A dependency on VEGF is attributed to its ability to regulate key processes throughout the angiogenic cascade, including endothelial cell migration, proliferation and protease expression (2)(3)(4), microvascular integrin expression (5), recruitment of endothelial cell precursors (6), capillary tube formation (7), neovascular survival (8), interactions with mural cells (9), and enhanced vascular permeability (10). The production of VEGF can be disproportionately up-regulated in tumors via oncogene activation (11), loss of tumor suppressor function (12,13), or changes in oxygen or glucose status (14). Tumor capillaries induced by overexpression of VEGF are tortuous and dilated (15); an architecture that is reminiscent of immature vessels during early vascular remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with previous research results, the present study indicates that the decrease in tumor-associated VEGF by SC-560 and taxol may be a crucial mechanism in controlling angiogenesis and inducing the inhibition of overall tumor growth. Studies showed that VEGF-positive tissue was associated with a high MVD expression, whereas VEGF-negative tissue demonstrated a low expression of MVD, indicating a positive correlation between VEGF and MVD (36,37). The increase of MVD, an indirect marker of intense tumor vascularization, increases blood volume (38), and increased MVD is known to be associated with both evolution of disease and survival (39)(40)(41).…”
mentioning
confidence: 99%